Air quality indicators through the use of liquens in the urban area in mining town of Itabira/MG Brazil (Research, Society and Development, 2020)
The mining town of Itabira/MG receives the dust, together with the particulate matter from the iron ore mines, located in the urban area. The quality of the air showed itself precarious because of the open-sky mining exercised by decades in the city. From this, comes up the necessity of making a research to verify the quality and contamination of the air of the city, complementing previous works. Thus, the general objective of the research was to evaluate the index of atmospheric pollution in mining town of Itabira, using the lichens as bio indicators. The method utilized was the passive bio monitoring from the use of lichens in four different points of the town. To the obtention of the results, was executed a field research with a quali-quantitative approach, observing the frequency and the types of lichens present over the cortex of the trees. The results were obtained through the analysis of the Pureness of the Air Index (PAI) calculated in each point. The quality of the air variated from mediocre to low and its contamination from medium to high. There was an improvement of this condition when the distance between the sampled point and the mining areas was greater, and when there was the presence of forests around the sampled points Stands out the impact that the mining activity exercise in the air quality and, consequently, in the human health.